Euripidea altera - Kovacs, David. (Mnemosyne, Supplements, 1996)
This volume, which continues the textual discussions section of the author's Euripidea (Brill, 1994), discusses those passages in Euripides' Heraclidae, Hippolytus, Andromache, Hecuba, Supplices, Electra, Heracles , and Troades - the plays of the author's Loeb Euripides, volumes Two and Three - where text or translation was in need of explanation or justification. A large number of new conjectures are proposed and some forgotten conjectures argued for.